낙동강 하구 모래갯벌에 서식하는 대형저서동물의 군집구조와 분포양상 - 서진영; 최진우; 신경순; Seo, Jin-Young; Choi, Jin-Woo; Shin, Kyoungsoon (한국해양생명과학회지, 2020)
This study was conducted to find the faunal composition and distribution patterns of macrobenthos where the sand tidal flat around barrier island at Nakdong River estuary in May, 2016 and 2017. The number of species ranged from 31 to 39, and density was from 789 to 1,644 ind.m-2 during the study period in the three tidal flats. The number of species and density were the highest in the tidal flat of Shinja-do and Jinwoo-do, respectively. The dominant species were Gammaridae unid. in amphipods of crustacea, Scoletoma heteropoda, Scoloplos armiger, Heteromastus filiformis, Prionospio japonica in polychaeta and Batillaria cumingii, Laternula marilina in mollusks from the three tidal flats. The proportion of carnivores such as crustacea and mollusks was higher in the upper part of the tidal flat, and polychaetes of deposit feeders, dominated in the middle and lower tidal flat. Overall, the intertidal macrobenthic communities in the study area showed a high proportion of carnivores. However, the sites where the mud content is high such as muddy sand sites, they showed a higher proportion of surface deposit feeders belonging to tube-builders which contribute to sediment stability. From this study, it seemed that the macrobenthic fauna of the sandy tidal flat at the Nakdong River estuary showed a similar fauna composition and zonal distribution patterns from those in other sandy tidal flats in Korea. 낙동강 하구 울타리섬 주변 갯벌에 서식하는 대형저서동물의 분포현황을 파악하기 위해 2016년과 2017년 5월에 신자도, 진우도, 을숙도에서 현장조사를 수행하였다. 조사 해역에서는 31~39종의 대형저서동물이 출현하였고, 서식밀도는 789~1,644 ind.m-2의 범위를 보였다. 출현종수는 신자도에서 가장 높았으나, 서식밀도는 신자도에서 가장 낮았고, 진우도에서 높게 나타났다. 본 연구 해역에서 출현한 대형저서동물의 주요 우점종은 갑각류의 Gammaridae unid., 다모류의 Scoletoma heteropoda, Scoloplos armiger, Heteromastus filiformis, Prionospio japonica, 연체동물의 댕가리(Batillaria cumingii), Laternula marilina 등이었다. 세 지역 모두 갯벌의 상부지역에서는 갑각류와 연체동물의 비중이 높았고, 하부로 갈수록 다모류의 비중이 다소 증가하는 경향을 보였다. 전체적으로 육식자의 비중이 높게 나타났으나, 니질 퇴적물의 함량이 높은 지역에서는 퇴적물 안정화에 기여하는 tube-builder가 속한 표층 퇴적물 식자의 비중이 다소 높게 나타났다. 낙동강 하구 모래갯벌의 대형저서생물상은 국내 다른 하구 모래갯벌이나 조간대 모래갯벌의 생물상과 유사한 종조성과 분포양상을 보였다.